2020
DOI: 10.1111/jopr.13161
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Accuracy of Implant Position Using Surgical Guides Fabricated by Additive and Subtractive Techniques

Abstract: Queiruga for your assistance in developing the measurement protocol and for providing training on GeoMagic software. Thank you to Kyle Bennett for his technical support in milling the surgical guides. Thank you to my co-residents for your help and sharing practical suggestions throughout the years of my study. I am also grateful to all the faculty, staff and dental assistants for their support and assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 73 publications
2
44
0
Order By: Relevance
“…In a study on the influence of two different printing materials for templates, no significant differences were found [13]. An in vitro study by Henprasert et al showed that the fabrication of the template in an additive or subtractive process had no influence on the implant position [12]. In contrast, Abduo and Lau demonstrated that templates produced through subtractive manufacturing led to more precise results [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on the influence of two different printing materials for templates, no significant differences were found [13]. An in vitro study by Henprasert et al showed that the fabrication of the template in an additive or subtractive process had no influence on the implant position [12]. In contrast, Abduo and Lau demonstrated that templates produced through subtractive manufacturing led to more precise results [39].…”
Section: Discussionmentioning
confidence: 99%
“…The manufacturing process for the drilling template can have an impact on the accuracy of the implant placement. Several studies have reported the influence of additive printing and subtractive processes, as well as of the materials used in these processes [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically sufficient accuracy and prosthetically predictable results can be achieved using this procedure [ 11 , 14 ]. Numerous studies on guided implant placement have attempted to determine the factors that affect the accuracy of the procedure, including different manufacturing methods or different materials used for drilling jigs [ 15 , 16 , 17 ]. Different drilling sleeves [ 18 , 19 , 20 ], as well as the intraoral positioning and fixation of the jigs [ 21 ], can influence accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…An implant planning software allows to import acquired radiographical and surface data and to visualize the final outcome, thereby facilitating to define the ideal implant site according to a virtual set-up and the anatomical characteristics of the patient [8,9]. Based on the virtually planned implant position, a surgical drilling guide can be manufactured, e.g., by 3D printing [10,11] and adapted to the clinical workflow without a typical learning curve [12]. Printing technology based on computer aided design and manufacturing (CAD-CAM) allows to create objects by adding consecutive layers [13].…”
Section: Introductionmentioning
confidence: 99%